The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00415-016-8220-2
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral microbleeds in early Alzheimer’s disease

Abstract: We hypothesize that cerebral microbleeds (CMB) in patients with different neuropsychological profiles (amnestic or non-amnestic) and MRI features of vascular damage could provide important information on the underlying pathological process in early Alzheimer's disease. The study was performed at two trial sites. We studied 136 outpatients with cognitive decline. MRI was performed using a magnetic field of 1.5 and 3 T. Neuropsychological assessment included Mini-Mental State Examination (MMSE), Montreal Cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…AD patients without CMBs ( n = 99) ( 48 ). The eighth study showed increased BBB dysfunction in the form of an increased CSF/serum albumin ratio in patients with cognitive decline with CMBs ( n = 15) compared with patients with cognitive decline but no CMBs ( n = 13) ( 50 ). In contrast, the last study could not identify any difference in BBB dysfunction measured as CSF/serum albumin ratios between AD patients with CMBs ( n = 26) and AD patients without CMBs ( n = 26) ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…AD patients without CMBs ( n = 99) ( 48 ). The eighth study showed increased BBB dysfunction in the form of an increased CSF/serum albumin ratio in patients with cognitive decline with CMBs ( n = 15) compared with patients with cognitive decline but no CMBs ( n = 13) ( 50 ). In contrast, the last study could not identify any difference in BBB dysfunction measured as CSF/serum albumin ratios between AD patients with CMBs ( n = 26) and AD patients without CMBs ( n = 26) ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…Damage to blood vessels can lead to pronounced BBB breakdown manifested as cerebral microbleeds (microhaemorrhages), which is frequently seen in AD 86–93 , MCI 94 , and in APOE*ε4 individuals who have increased genetic risk of AD 94 . CAA is one of the main causes of vascular degeneration and lobar microbleeds in AD, and contributes to BBB breakdown, infarcts, white matter changes and cognitive impairment 26 .…”
Section: Neuroimaging Evidence Of Bbb Disruptionmentioning
confidence: 99%
“…Amyloid deposition in the brain, as detected by 18 F-florbetapir PET, is positively associated with the number of microbleeds in individuals with MCI and AD 99 . Several studies that reported a high prevalence of microbleeds in patients with AD 86–93 or MCI 94 did not perform amyloid-PET imaging 86–93 , however, precluding a direct comparison of microbleeds and CAA severity.…”
Section: Neuroimaging Evidence Of Bbb Disruptionmentioning
confidence: 99%
“…The gradual spreading of the intracellular aggregation of hyperphosphorylated tau (P-tau) in the brain is associated with AD progression [ 1 ]. Studies also reveal the association between cerebral microbleeds and P-tau [ 33 , 34 ]. Interestingly, our data did not reveal increased hemorrhagic stroke in both AD and DLB patients when compared to NC individuals.…”
Section: Discussionmentioning
confidence: 99%